The Physical Activity Environment Policy Index (PA-EPI): a Tool for Monitoring and Benchmarking Government Policies Promoting Physical Activity - Woods, Catherine B.; Kelly, Liam; Volf, Kevin; Gelius, Peter; Messing, Sven; Forberger, Sarah; Lakerveld, Jeroen; Den Braver, Nicolette R.; Zukowska, Joanna; Bengoechea, Enrique García (Book of Abstracts, 2022)
Background: To improve population levels of physical activity (PA), a multifaceted response, including government action, is essential. The purpose of this study was to develop the ‘Physical Activity Environment Policy Index’ (PAEPI) monitoring framework which allows for the assessment of government policies and actions. Methods: An iterative process was undertaken. This involved a review of policy documents, a policy audit of four European countries, systematic reviews of scientific literature, an online consultation with academic experts (N=101; 20 countries) and policymakers (N=40; 4 countries), and consensus workshops. Findings: The PA-EPI is conceptualised as a two-component framework. The two components comprise eight ‘policy’ and seven ‘infrastructure support’ domains. The policy domains are education, transport, urban design, healthcare, public education, sport-for-all, workplaces and community. The infrastructure support domains are leadership, governance, monitoring and intelligence, funding and resources, platforms for interaction, workforce development, and health-in-all-policies. Across all domains, the PA-EPI includes forty-five ‘good practice statements’ (GPS). Discussion: The PA-EPI is the first attempt at using knowledge co-production at the science–policy interface to create a policy index to assess the healthiness of the PA environment. From a social science perspective, it is grounded in evidence pertaining to the importance of specific settings for population-level physical activity behaviour. Its design reflects theories pertaining to the policy cycle and on policy instruments. Conclusion: Once pre-tested and piloted in several countries of various sizes and income levels, the PA-EPI GPS will evolve into benchmarks established by governments at the forefront of creating and implementing policies to address inactivit